WEBSITE DESIGN APPLICATIONS CHRISYE BIOGRAPHY USING MICROSOFT FRONTPAGE 2003 - Ana Yoeni Kurniati; Yuce Yuliani, SKom, MMSI (Jurnal Sistem Informasi, 2003)
Media information is a means to convey a message orinformation that we can receive both spoken and written, and various kinds such asnewspapers, television, radio, and computers. Information plays a very important forhuman life. Information needed is information that must be very fast, accurate, andaccountable authenticated by many, especially among people for business,entertainment, and various other information. The Internet is a global collection of(global) network of thousands of computers and millions of personal computers thatrun independently. Internet easy to use by anyone, even those who only have aminimal capacity. Web is an information delivery using Internet technology. With theweb, we can interact in a vast space. Until now, the website is very popular, but itsuse required a design.